Pergeseran dan Pemertahanan Bahasa Ibu Dalam Ranah Rumah Tangga Migran di Kota Semarang - Mujid F Amin; Suyanto Suyanto (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2017)
This study aims to explain the pattern of language selection in speech acts between Indonesian language and mother tongue of migrants; Explaining the migration process of migrant language; Identify and explain the pattern of migrant language shift in Semarang City; and explains the contributing factors of shifting and maintaining the language of migrants. Sampling using cluster sampling technique followed by random sampling. Data collection using observation or referring method, stereo interview, and in-depth interview. Data analysis used descriptive statistics (single and cross frequency distribution table) and qualitative descriptive. Qualitative analysis by means of categorical analysis followed by theoretical meanings and conclusions. The results of this study indicate a shift in mother tongue in the domestic realm. Most of the migrants in Semarang City use Bahasa Indonesia more often than their mother tongue. However, there are some migrants who still maintain their mother tongue among the traditional migrants residing in the kampong area. In the family domain, married migrants whose mother tongue is the same as the mother tongue (husband or wife), are more likely to use a combination of mother tongue and Indonesian to communicate in both family and family affairs.